Potential of Pseudomonads Fluorescents as Plant Disease Biocontrol Agents - Rusendra, Nabilla Makra; Advinda, Linda; Chatri, Moralita; Handayani, Dezi (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Fluorescent pseudomonas are a group of rhizobacteria that colonize plant root areas and have potential as biocontrol agents for plant diseases that can be developed. This group of bacteria can increase plant growth by producing growth hormones, one of which is producing hormones Indole Acetic Acid (IAA), solubilizing phosphate, and siderophores. Apart from that, fluorescent pseudomonas are also able to induce plant resistance by producing secondary metabolite compounds which have antimicrobial properties. Many studies have shown that one of the most abundant microorganisms in the rhizosphere (around the roots) is bacteria Pseudomonas spp. This review will discuss the occurrence, distribution, growth studies, mechanisms of action, and control of plant diseases by fluorescent pseudomonad bacteria. This literature review will be helpful for future research aimed at providing information that fluorescent pseudomonads have potential as biocontrol agents for plant diseases.